Danube River Discharge at Bezdan Gauging Station (Serbia) and its correlation with Atmospheric Circulation Patterns - Dolinaj, Dragan; Leščešen, Igor; Pantelić, Milana; Urošev, Marko; Milijašević Joksimović, Dragana (Geographica Pannonica, 2019)
For understanding hydroclimatological process chain it is crucial to identify relations between large-scale climatic circulations and river discharge. The Danube is one of the most important European waterways, flowing 2.857 kilometers across the Europe and with 817.000 km2 basin. Danube River average and maximum discharges are correlated with eight atmospheric circulation patterns indices: AOi, EAi, EA/WRi, ENSOi, MOi, NAOi, SCANDi and WeMOi in 65 years period at the Bezdan gauging station in Serbia. Obtained results showed that precipitation, MOi and WeMOi have constant and dominant influences on Danube River average discharge at Bezdan gauging station, while maximum discharge is mainly influenced by precipitation and MOi. All registered correlations are positive.